The influence of Ti ultrathin insertion layer on the effective magnetic damping and effective spin Hall angle - Xu, Zhan (2023)
We report the influence of ultrathin Ti insertion layer on the effective magnetic damping and effective spin Hall angle in Co/[Pt/Ti]n/Pt structures via spin-torque ferromagnetic resonance measurements. The effective magnetic damping shows a non-monotonic variation as a function of insertion layers number n, reaching a minimum at n = 5. Our analysis shows that when n is less than 5, the damping is mainly related to the thickness of the bottom Pt layer, and when it is greater than 5, the attenuation of the spin currents leads to increased damping. The effective magnetic damping first decreases as the number of layers n increases, reaching a minimum at n=5, and then increases with further increases in n. The observation can be ascribed to a competition between the increased longitudinal resistivity, which is due to the strong interfacial scattering, and the reduced effective spin Hall conductivity that originates from the shortening of the carrier lifetime. Additionally, the extracted interfacial spin transparency is found to be improved with the effect of the insertion layer.